2019
DOI: 10.3390/ijms20174132
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Autophagy Regulated by Sirt1/FoxO1 Pathway on the Release of Factors Promoting Thrombosis from Vascular Endothelial Cells

Abstract: Factors promoting thrombosis such as von Willebrand factor (vWF) and P-selectin are essential for the development of atherosclerosis (AS) and arterial thrombosis. The processing, maturation and release of vWF are regulated by autophagy of vascular endothelial cells. The Sirt1/FoxO1 pathway is an important pathway to regulate autophagy of endothelial cells, therefore the Sirt1/FoxO1 pathway may be an important target for the prevention of thrombosis. We investigated the role of ox-LDL in the release of vWF and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 30 publications
5
45
0
Order By: Relevance
“…However, in the present study, the autophagy inhibitor CQ did not affect the expression of p-FoxO1 in INS-1 cells. The current results were consistent with previously reported findings that the effect of autophagy can be regulated by FoxO1 but the autophagy inhibitor 3-methyadenine had no effect on FoxO1 in vascular endothelial cells ( 19 ). These results indicated that FoxO1 improved the viability of INS-1 cells against PA by upregulating the expression of autophagy-associated proteins.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, in the present study, the autophagy inhibitor CQ did not affect the expression of p-FoxO1 in INS-1 cells. The current results were consistent with previously reported findings that the effect of autophagy can be regulated by FoxO1 but the autophagy inhibitor 3-methyadenine had no effect on FoxO1 in vascular endothelial cells ( 19 ). These results indicated that FoxO1 improved the viability of INS-1 cells against PA by upregulating the expression of autophagy-associated proteins.…”
Section: Discussionsupporting
confidence: 93%
“…In db/db mouse model, FoxO1 knockout decreases glucose-responsive insulin secretion ( 18 ). Moreover, FoxO1 regulates autophagic flux in various cell types, such as vascular endothelial cells ( 19 ), human cholangiocarcinoma QBC939 cells ( 15 ) and rat mesangial cells ( 20 ). However, the effect of FoxO1 on autophagy in pancreatic β-cell has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Except Resveratrol used in this study, the old drug metformin may alleviate oxidative stress and enhances autophagy in diabetic kidney disease via AMPK/SIRT1-FoxO1 pathway [35], and by enhancing autophagy ux and decreasing the release of vWF and P-selectin. The Sirt1/FoxO1 pathway is also a promising target to prevent atherosclerosis (AS) and arterial thrombosis [36]. Similar to aging and mechanical stress-induced chronic in ammatory diseases in kidney and cardiovascular system, our previous reports [19] and current observations suggested that Sirt1 possibly protected against injury-induced OA with aging via SIRT1/FoxO1/autophagy during OA progress.…”
Section: Discussionmentioning
confidence: 59%
“…Murine SIRT1 deficiency leads to increased NF-κB acetylation and activation, reduced KLF2 and thrombomodulin protein expression, and elevated fibrin generation in the lung along with reduced expression of tissue factor pathway inhibitor (TFPI) and increased PAI-1 activity. A recent study by Wu et al showed that SIRT1 dependent deacetylation of transcription factor forkhead box protein O1 (FOXO-1) enhances autophagy, therefore reducing oxidized low-density lipoprotein (ox-LDL)-induced endothelial secretion of Von Willebrand factor and P-selectin, two critical proteins for thrombus formation [ 77 ]. In addition, the role of SIRT1 has also been implicated in deep vein thrombosis [ 78 ].…”
Section: Roles Of Mas Receptor Pgi 2 and Sirt1 mentioning
confidence: 99%